The Role of Teaching Idioms and Proverbs in Mitigating Communication Breakdown in ICC - HADEDDOU, Aisha (My University, 2020)
Learning a foreign language has long been focusing on learning the linguistics codes. However, the recent emphasis nowadays has turned to be on cross-cultural communication and this leads to the incorporation of both linguistic and cultural learning in the EFL classroom in order to interact appropriately cross cultures. For that reason, the aim of his study is to investigate the extent to which integrating culturally-bound expressions as idioms and proverbs help EFL learners to mitigate communication breakdown, and whether they are aware of the role of those expressions. In order to conduct this research, two tools were used : a questionnaire and interview to collect qualitative and quantitative data. The results of this study reveal that although that cultural aspects are integral part in learning and teaching processes, EFL learners are not aware enough of the use of such idioms and proverbs. Finally, this research work tied to highlight a list of helpful recommendations for learners to develop their awareness about idioms and proverbs in order to an intercultural competent communicator.
The Case of Master Students of English at Abdelhamid Ibn Badis University, Mostaganem
Keywords: Cross-cultural communication; Culturally-bound expressions; Idioms; Proverbs; Communication breakdown; Intercultural competent communicator